Assessment of Guideline Adherence and Hypertension Control in a Tertiary Care Hospital in Calicut - KS, Vishnudas; S, Swetha; Chacko, Sheba Susan; Solemn, Angel; P, Silsha; Suresh, Arumukhan; Babu, Ganapathi (Journal of Pharmacy Practice and Community Medicine)
Objectives: To evaluate the effect of guideline adherence in treatment of hypertension in a tertiary care hospital in Calicut. Materials and Methods: A prospective observational study was conducted for a period of 6 months with a follow up of 81 hypertensive prescriptions among 100 patients, who were admitted in PVS Hospital, Calicut. BP was the parameter assessed on the baseline and follow up after one month. The effects of empirical treatment were compared with treatment based on JNC 8 guideline. Results: In a total of 81 prescriptions, 32 (39.5%) prescriptions were found in the age group of ≤60 years, in which 12 (37.5%) were males and 20 (62.5%) were females and 49 (60.5%) prescriptions were comes under the age group of >60 years, in which 34 (69.39%) were males and 15 (30.61%) were females. Among monotherapy, 14 (35%) prescriptions had ARBs as antihypertensive drug followed by diuretics 12 (30%), beta blockers 6 (15%), ACE Inhibitors 4 (10%) and Calcium Channel Blockers 4 (10%). About 59.26% of the medical records showed good level of JNC- 8 guideline adherence. This adherence has significant negative association only with diabetes mellitus comorbidity (p=0.0152, Ø= -0.241) not with other co morbidities. Among 81, 69 (85.18%) patients were on goal BP on second visit. However BP control have a positive association with guideline adherence (p= 4.6E-05, Ø=0.275) and negative association with mono therapy (p<0.01, Ø= -0.108). Conclusion: Prescribing practices were fairly compliant with guidelines. Doctors poorly adhered to guidelines in hypertensive patients with Diabetes. Significantly better hypertension control was seen in patients who were on guideline adherent therapy.
Keywords: JNC 8 Guideline; Adherence; BP control; Monotherapy; Co Morbidity; Antihypertensive.